PENERAPAN LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK ASERTIVE UNTUK MENGURANGI KECEMASAN BERKOMUNIKASI SISWA SMAN 10 KOTA JAMBI - Khairunnisa Khairunnisa; Nelyahardi Gutji; Muhammad Ferdiansyah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
The background of this research is based on phenomena in the field carried out by researchers at SMA N 10 Jambi City, there are several students who experience communication anxiety. Symptoms that can be seen directly are students who are nervous in their opinions, not confident, and embarrassed. The communication anxiety factor is because of the fear of being wrong and not confident, and the fear of being laughed at by other students. This research aims to find out how to apply group guidance services with assertive techniques to reduce students' communication anxiety. The theoretical benefit of this research is that it can be used to develop scientific literature, especially guidance and counseling, while practically it is divided into 3, namely for guidance and counseling teachers, students and researchers.This type of research is Service Action Research (PTL) in group guidance services with assertive techniques. This research was carried out in 3 cycles, where in one cycle there were 2 meetings and each cycle consisted of planning, implementation, evaluation and reflection. To see the process of each cycle, there are questionnaire sheets filled in by students and observation sheets filled out by collaborators. Based on the results obtained after the implementation of cycle I, meeting I, it was 79%, then cycle I, meeting II, 72%, in cycle II, meeting I, 61%, cycle II, meeting II, 59%, continued in cycle III, meeting I, 55%, in cycle III, meeting II reduced to 35%. There is a decrease in communication anxiety each cycle so that assertive techniques with group guidance services can reduce students' communication anxiety.